Biodegradable Electrospun Scaffolds as an Emerging Tool for Skin Wound Regeneration: A Comprehensive Review - Deepika Sharma; Shriyansh Srivastava; Sachin Kumar; Pramod Kumar Sharma; Rym Hassani; Hamad Ghaleb Dailah; Asaad Khalid; Syam Mohan (Pharmaceuticals, 2023)
Skin is designed to protect various tissues, and because it is the largest and first human bodily organ to sustain damage, it has an incredible ability to regenerate. On account of extreme injuries or extensive surface loss, the normal injury recuperating interaction might be inadequate or deficient, bringing about risky and disagreeable circumstances that request the utilization of fixed adjuvants and tissue substitutes. Due to their remarkable biocompatibility, biodegradability, and bioactive abilities, such as antibacterial, immunomodulatory, cell proliferative, and wound mending properties, biodegradable polymers, both synthetic and natural, are experiencing remarkable progress. Furthermore, the ability to convert these polymers into submicrometric filaments has further enhanced their potential (e.g., by means of electrospinning) to impersonate the stringy extracellular grid and permit neo-tissue creation, which is a basic component for delivering a mending milieu. Together with natural biomaterial, synthetic polymers are used to solve stability problems and make scaffolds that can dramatically improve wound healing. Biodegradable polymers, commonly referred to as biopolymers, are increasingly used in other industrial sectors to reduce the environmental impact of material and energy usage as they are fabricated using renewable biological sources. Electrospinning is one of the best ways to fabricate nanofibers and membranes that are very thin and one of the best ways to fabricate continuous nanomaterials with a wide range of biological, chemical, and physical properties. This review paper concludes with a summary of the electrospinning (applied electric field, needle-to-collector distance, and flow rate), solution (solvent, polymer concentration, viscosity, and solution conductivity), and environmental (humidity and temperature) factors that affect the production of nanofibers and the use of bio-based natural and synthetic electrospun scaffolds in wound healing.